CsLFY is required for shoot meristem maintenance via interaction with WUSCHEL in cucumber (Cucumis sativus). Issue 1 (23rd December 2017) - Zhao, Wensheng; Chen, Zijing; Liu, Xiaofeng; Che, Gen; Gu, Ran; Zhao, Jianyu; Wang, Zhongyi; Hou, Yu; Zhang, Xiaolan
Summary: Cucumber ( Cucumis sativus ) is an agronomically important vegetable with indeterminant growth habit, in which leaves are produced from the shoot apical meristem (SAM), and unisexual flowers are generated from the leaf axils. LEAFY ( LFY ) and its homologs have been shown to play important roles in promoting flower development and branching. The LFY homolog gene CsLFY was cloned in cucumber. Molecular biology, developmental biology and biochemical tools were combined to explore the biological function of the LFY homologous gene CsLFY in cucumber. CsLFY was expressed in the SAM, floral meristem and floral organ primordia. Ectopic expression of CsLFY rescued the phenotype of the lfy‐5 mutant in Arabidopsis . Knockdown of CsLFY by RNA interference (RNAi) led to defective shoot development and premature discontinuance of leaf initiation in cucumber. Transcription of CsWUS and putative CsLFY target genes including CsAP3 and CUM1 were significantly reduced in the CsLFY ‐RNAi lines. Further biochemical analyses indicated that CsLFY physically interacts with CsWUS in cucumber. These data suggested that CsLFY has a novel function in regulating shoot meristem maintenance through interaction with CsWUS, and promotes flower development via activation of CsAP3 and CUM1 in cucumber.